2021
DOI: 10.1155/2021/6789835
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Radix Rhei Et Rhizome Intervention in Cerebral Infarction: A Research Based on Chemoinformatics and Systematic Pharmacology

Abstract: Objective. To explore the therapeutic targets, network modules, and coexpressed genes of Radix Rhei Et Rhizome intervention in cerebral infarction (CI), and to predict significant biological processes and pathways through network pharmacology. To explore the differential proteins of Radix Rhei Et Rhizome intervention in CI, conduct bioinformatics verification, and initially explain the possible therapeutic mechanism of Radix Rhei Et Rhizome intervention in CI through proteomics. Methods. The TCM database was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 111 publications
(136 reference statements)
1
0
0
Order By: Relevance
“…Analysis of Clec14a Cre ER T2 X Ncam1 fl/fl mice demonstrated reduced vessel density in Cre+ mouse bones and diminished endothelial cell proliferation (Figure 3D), consistent with earlier studies implicating NCAM-1 in the regulation of endothelial cell proliferation through the PI3K-AKT signalling pathway (Xiang et al, 2021).…”
Section: Anabolic Ncam-1-1433ζδ-derived-peptide Interaction Drives An...supporting
confidence: 90%
“…Analysis of Clec14a Cre ER T2 X Ncam1 fl/fl mice demonstrated reduced vessel density in Cre+ mouse bones and diminished endothelial cell proliferation (Figure 3D), consistent with earlier studies implicating NCAM-1 in the regulation of endothelial cell proliferation through the PI3K-AKT signalling pathway (Xiang et al, 2021).…”
Section: Anabolic Ncam-1-1433ζδ-derived-peptide Interaction Drives An...supporting
confidence: 90%
“…RR is commonly used to treat acute IS based on Tong Fu's theory of TCM. Previous studies have demonstrated that RR might exert a neuroprotective effect in cerebral ischemia by developing synaptic plasticity, inhibiting neuro-inflammation, and regulating the blood-brain barrier [16,17,39]. However, the mechanism of RR in the treatment of IS has not been completely elucidated due to the complexity of chemical components and the diversity of action targets of herbs.…”
Section: Discussionmentioning
confidence: 99%